(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ovarian cyst is commonest problem facing by young women and foremost cause of infertility in women. Sedentary lifestyle, abnormal food habits, stressful life have influences on secretion of female hormones and thereby causing the manifestation of ovarian cyst. Methodology: In this present case study, 18 years old woman patient consulted to the OPD of Kayachikitsa of GAMCH, Bareilly with the complaints of pain in lower abdomen, irregular menses and generalized weakness. Ultrasonography was advised and finding suggestive of right ovarian cyst (37×33mm). She was given combination of traditional herbomineral Ayurvedic medicine for three months 20 days. Result: By the use of combination of traditional Ayurvedic medicines complete resolution of ovarian cyst was noticed in follow up- Ultrasonography. Discussion: This case study highlights on the management of ovarian cyst by Ayurvedic medicine.